How far are we from the slippery slope? The Laffer curve revisited - Mathias Trabandt; Harald Uhlig (European Central Bank (ECB), 2010)
We characterize the Laffer curves for labor taxation and capital income taxation quantitatively for the US, the EU-14 and individual European countries by comparing the balanced growth paths of a neoclassical growth model featuring ”constant Frisch elasticity” (CFE) preferences. We derive properties of CFE preferences. We provide new tax rate data. For benchmark parameters, we find that the US can increase tax revenues by 30% by raising labor taxes and 6% by raising capital income taxes. For the EU-14 we obtain 8% and 1%. Denmark and Sweden are on the wrong side of the Laffer curve for capital income taxation.
Keywords: E0; E60; H0; 330; dynamic scoring; incentives; Laffer curve; US and EU-14 economy; Steuerpolitik; Steuerbelastung; Arbeit; Kapital; Laffer-Kurve; Neoklassische Theorie; Steuersenkung; Theorie; EU-Staaten; USA